The Geological process behind the archeological sites in the Espinhaço Meridional (Revista Espinhaço, 2019)
The southern Espinhaço range, an important physiographic landmark in Minas Gerais territory, hosts a vast network ofarchaeological sites, whose material and cultural collection have been crucial for investigating the early americans. Most of these sites occur in natural rock shelters such as ridges and caves, developed in precambrian metasedimentary rocks. This paper aims to present, in a didactic way, the main geological processes involved in the genesis of these shelters. The sedimentation, diagenesis, metamorphism and deformation processes influence the composition and structure of the rocks, and these characteristics, in turn, exert strong control over the weathering and erosion processes that, ultimately, give rise to the relief forms that favor human occupation. This demonstrates an intimate relationship between the inorganic and the organic, between the geological and the anthropological, in time and space, in an excellent example of interaction between the various and complex elements of the Earth System.
Keywords: Espinhaço range; Archaeology; Geology